The performance of midwives in early detection of cervical cancer using visual inspection test with acetic acid - Deviati Juwita Sari; Pudji Lestari; Pungky Mulawardhana (Universitas Airlangga, 2022)
HIGHLIGHTS 1. Visual Inspection with Acetic Acid (VIA) method is used in midwifery for early detection of cervical cancer. 2. Service period, knowledge, and attitudes are factors that affect a midwife's performance in using VIA method for cervical cancer detection.   ABSTRACT Objective: This study examined the association between service period, knowledge, and attitudes toward the performance of midwives in the early detection of cervical cancer using the Visual Inspection with Acetic Acid (VIA) method in Banjarmasin, Indonesia. Materials and Methods: This is a cross-sectional study done in 26 Public Health Centers in Banjarmasin, Indonesia, from March to November 2020 involving 172 respondents. Samples were purposively selected using a non-probability sampling technique. Data collection instruments were questionnaire and Health Service reports. Data analysis was done computerized. Results: Out of 172 respondents, 67.4% of which had  > 10 years of service period, 67.4% had inadequate knowledge and 86% showed a positive attitude about early detection of cervical cancer using the IVA method, and 79.9% had poor performance in conducting early detection of cervical cancer using the IVA method. Results of Chi-square test showed the associations between the service period (p = 0.005), knowledge (p = 0.0001), and attitude (p = 0.005) with the performance of midwives in early detection of cervical cancer using the VIA method. Conclusion: Service period, knowledge, and attitudes were associated with the performance of midwives in the early detection of cervical cancer using the VIA method in Banjarmasin, Indonesia. Professional training programs should be taken into consideration in improving the performance of midwives in cervical cancer detection.